Nonprescription antimicrobial use during the COVID-19 pandemic: a systematic review - Karolina, Sinta; Sulistiadi, Wahyu (Universitas Gadjah Mada, 2023)
Purpose: Restrictions on mobility, confusion of information, and the lack of scientific evidence related to the treatment of COVID-19 have implications for the emergence of self-medication behavior in the community, especially the use of antimicrobials without a prescription. This study aims to describe the pattern of non-prescription antimicrobial use during the COVID-19 pandemic. Methods: A systematic review was conducted on articles published between 2020-2022 from 3 databases: Embase, Scopus, and Science Direct, examining the use of over-the-counter antimicrobials during the COVID-19 pandemic. Results: 13 relevant studies reviewed usage patterns, including self-medication behavior and antimicrobial dispensing practices without a prescription. Conclusion: The panic during the COVID-19 pandemic triggered the over-the-counter use of antimicrobials without a prescription, both as an effort to prevent and reduce symptoms. The role of community pharmacists and the government is urgently needed to overcome this.